PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP PERENCANAAN KARIER SISWA - Sulusyawati, Heni (Jurusan Bimbingan dan Konseling, 2021)
This research is motivated by the finding of students who are still confused in choosing a major to enter higher education. The purpose of this study was to describe the effect of peer social support on student career planning. This type of research is a qualitative descriptive study, using a natural setting approach, which places more emphasis on what the informants experience naturally. Determination of informants in this study using purposive sampling method. Collecting data using observation, interview, documentation, and tri-accounting techniques. Data analysis uses the Miles Hurberman method, in which Miles Huberman divides 3 stages in data analysis, namely data reduction, display data, and conclusion drawing / verification. The results showed that there was an effect of peer social support on student career planning, it was shown from emotional support, support, appreciation, information support.